From Usul Fiqh to Modern Islamic Legal Theory: The Transformation of Legal Discovery Methodology in the Islamic Intellectual Tradition - Azka Rayyani; Eka Putra Zakran; Maya Surya (Jurnal Cendikia ISNU SU, 2025)
The development of modern society has given rise to increasingly complex legal issues, thus demanding reforms in the methodology for discovering Islamic law. In the classical Islamic intellectual tradition, ushul fiqh serves as the primary methodological framework for understanding and establishing law derived from the Qur'an and Sunnah. This study aims to analyze the transformation of the methodology for discovering law from the classical ushul fiqh framework to the development of modern Islamic legal theory within the Islamic intellectual tradition. This study employed library research with historical and normative approaches. Data were obtained through a review of classical ushul fiqh literature and the works of modern Islamic legal thinkers. The historical approach was used to trace the development of the methodology for establishing law within the Islamic tradition, while the normative approach was used to analyze methodological concepts in Islamic legal theory and their relevance to contemporary issues. The results show that classical ushul fiqh developed a methodology for discovering law oriented toward textual analysis of the sources of revelation and the use of legal analogy as a rational instrument in expanding the scope of law. However, the complexity of modern issues has given rise to criticism of the limitations of this approach. In the development of contemporary thought, modern Islamic legal theory seeks to integrate the maqasid al-shariah approach, the principle of benefit, and social analysis as a more contextual methodological framework in the process of legal discovery. This study concludes that the transformation of legal discovery methodology within the Islamic tradition is a process of intellectual evolution aimed at maintaining the relevance of Islamic law in the face of changing times. Therefore, the development of Islamic legal methodology needs to continue to be directed towards integrating normative principles of sharia with analysis of the social realities of modern society.